Localized N20 Component of Somatosensory Evoked Magnetic Fields in Frontoparietal Brain Tumor Patients Using Noise-Normalized Approaches - Elaina, N.S. (Urban und Vogel GmbH, 2018)
Purpose: To localize sensorimotor cortical activation in 10Â patients with frontoparietal tumors using quantitative magnetoencephalography (MEG) with noise-normalized approaches. Material and Methods: Somatosensory evoked magnetic fields (SEFs) were elicited in 10Â patients with somatosensory tumors and in 10Â control participants using electrical stimulation of the median nerve via the right and left wrists. We localized the N20m component of the SEFs using dynamic statistical parametric mapping (dSPM) and standardized low-resolution brain electromagnetic tomography (sLORETA) combined with 3D magnetic resonance imaging (MRI). The obtained coordinates were compared between groups. Finally, we statistically evaluated the N20m parameters across hemispheres using non-parametric statistical tests. Results: The N20m sources were accurately localized to Brodmann areaÂ 3b in all members of the control group and in seven of the patients; however, the sources were shifted in three patients relative to locations outside the primary somatosensory cortex (SI). Compared with the affected (tumor) hemispheres in the patient group, N20m amplitudes and the strengths of the current sources were significantly lower in the unaffected hemispheres and in both hemispheres of the control group. These results were consistent for both dSPM and sLORETA approaches. Conclusion: Tumors in the sensorimotor cortex lead to cortical functional reorganization and an increase in N20m amplitude and current-source strengths. Noise-normalized approaches for MEG analysis that are integrated with MRI show accurate and reliable localization of sensorimotor function. Â© 2017, Springer-Verlag Berlin Heidelberg.